PENGEMBANGAN PEMASARAN UMKM MELALUI SOSIAL MEDIA BAGI MASYARAKAT DI KELURAHAN GAJAH MUNGKUR KOTA SEMARANG - Widodo, Untung; Widowati, Madu Retno; Tasriastuti, Nurohmi Ambar (STIE Pelita Nusantara, 2025)
This community service activity aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in utilizing social media as a tool for digital marketing. The activity was conducted in Gajah Mungkur Subdistrict, Semarang City, targeting MSME actors who have not yet optimized their product marketing through digital means. The methods employed included training and direct assistance on digital marketing strategies using platforms such as Instagram, Facebook, and WhatsApp Business. The results showed an improvement in the participants' understanding and skills in creating promotional content, managing business social media accounts, and identifying online target markets. This program is expected to help MSMEs increase their competitiveness and expand their market reach.Keywords : MSMEs, digital marketing, social media, community service, Semarang